Tentative Screening Procedure for Selecting Bright and Slow Children in Kindergarten. - Kirk, Winifred D. (Exceptional Children, 1966)
In an effort to develop a more efficacious screening device for selecting bright and slow kindergarten children, four hypotheses were tested: (a) that teachers are subject to a CA bias, selecting older children as bright and younger children as slow; (b) that teachers can make a more accurate judgment of young children's ability by evaluating a child's ability in a number of specific areas to procure a composite score; (c) that a still more accurate estimate can be made by making a mechanical adjustment for CA and applying it to the composite score; and (d) that such an adjusted score can be successfully utilized as a screening device in selecting bright and slow children. The first three hypotheses were supported by the data, but the data were equivocal in relation to the last hypothesis.